The finite element method : theory, implementation, and applications - Larson, Mats G. 1968-; Bengzon, Fredrik (New York : Springer, 2013)
Introducing the finite element method as a general computational method for solving partial differential equations approximately, this book goes on to cover important applications including diffusion and transport phenomena, solid and fluid mechanics and more.--
Includes bibliographical references (pages 379-381) and index.
Keywords: Finite element method; Finite element method